Phenotype of early-onset fetal growth restriction in sheep - Sutherland, Amy E.; White, Tegan A.; Rock, Charmaine R.; Piscopo, Beth R.; Dudink, Ingrid; Inocencio, Ishmael M.; Azman, Zahrah; Pham, Yen; Nitsos, Ilias; Malhotra, Atul; Yawno, Tamara; Polglase, Graeme R.; et al. (Frontiers in Endocrinology, 2024)
Introduction Fetal growth restriction (FGR) is a common pregnancy complication, caused by placental insufficiency, with serious adverse consequences for development in utero and postnatal wellbeing. There are no antenatal treatments to improve growth or organ development in FGR, and animal models are essential to mimic the physiological adaptations in FGR and to assess potential interventions. This study aimed to identify the temporal nature of reduced developmental trajectory in fetuses with FGR, and to examine the effects of common factors that may mediate differential growth such as glucocorticoid treatment. We hypothesised that the trajectory of growth would be adversely impacted by FGR. Methods FGR was induced via surgical placental insufficiency in fetal sheep (89 days gestation/0.6 gestation; n=135) and compared to age-matched controls over the last third of gestation and into neonatal life (n=153). Results Body weight of FGR fetuses/lambs was significantly reduced compared to controls (p<0.0001) from 127 days of gestation (term is 148 days), with increased brain:body weight ratio (p<0.0001) indicative of brain sparing. All biometric measures of body size were reduced in the FGR group with the exception of biparietal (head) diameter. The trajectory of body growth in the last trimester of sheep pregnancy was significantly reduced in the FGR group compared to controls, and stillbirth rate increased with longer gestation. Discussion This work provides a well characterised FGR animal model that mimics the known physiological adaptations in human pregnancy and can be used to determine the efficacy of potential interventions.